2018
DOI: 10.1038/s41598-018-22736-5
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of β-lactam antibiotic on lysozyme capped gold nanoclusters retrogress MRSA and its persisters following awakening

Abstract: In this study we have reported an efficient antibacterial hybrid fabricated through surface functionalization of lysozyme capped gold nanoclusters (AUNC-L) with β-lactam antibiotic ampicillin (AUNC-L-Amp). The prepared hybrid not only reverted the MRSA resistance towards ampicillin but also demonstrated enhanced antibacterial activity against non-resistant bacterial strains. Most importantly, upon awakening through cis-2-decenoic acid (cis-DA) exposure, the MRSA persister got inhibited by the AUNC-L-Amp treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 56 publications
0
44
0
Order By: Relevance
“…S. Kalita et al . 86 reported that AuNPs are biocompatible towards mammalian cells and have antibacterial properties. As metallic nanoparticles, they are used in small doses because of their controlled release effect, thereby diminish any proposed cytotoxicity by reducing the necessity for high doses.…”
Section: Discussionmentioning
confidence: 99%
“…S. Kalita et al . 86 reported that AuNPs are biocompatible towards mammalian cells and have antibacterial properties. As metallic nanoparticles, they are used in small doses because of their controlled release effect, thereby diminish any proposed cytotoxicity by reducing the necessity for high doses.…”
Section: Discussionmentioning
confidence: 99%
“…One of the reasons was possibly caused by their antibacterial effect. 52 This antibacterial effect of Lys-AuNCs during the proliferation of osteoblast will be further investigated in the future. Meanwhile, they increased protein expressions such as Col-1 and ALP, which can promote PI3K/Akt signaling pathways.…”
Section: Inhibition Of Osteoclastogenesismentioning
confidence: 96%
“…In addition, some Au NCs possess inherent antibacterial activity, and may exert certain polyvalent and synergistic effects through antibiotic loading to enhance the antibacterial activity of nanosystems . For example, Kalita et al developed a potent antibacterial hybrid prepared through surface functionalization of lysozyme-capped Au NCs (Lys-Au NCs) with β-lactam antibiotic ampicillin (Lys-Au NCs-Amp) (Kalita et al, 2018). The antibacterial hybrid not only reverses the MRSA resistance toward ampicillin but also exhibits enhanced antimicrobial activity against non-resistant bacterial strains.…”
Section: Antibiotic-au Ncs Systemsmentioning
confidence: 99%